Adaptive and harmful autobiographical remembering after the loss of a loved one. (1st February 2023) - Wolf, Tabea; Strack, Veronika; Bluck, Susan
Abstract: Objectives: Remembering one's personal past serves psychosocial functions. Adaptive use of autobiographical memory is related to well-being but little research has focused on grief. We address this in two studies theoretically grounded in the model of reminiscence and health. Method: Participants were adults who were actively grieving, and in both studies, completed the Reminiscence Functions Scale and grief-related measures (i.e. feelings of grief, positive changes in life perspective). Study 1 focused on uses for generally recalling one's past and Study 2 on uses of memories of the deceased. Results: Across studies, self-negative ways of remembering were associated with stronger feelings of grief and also mediated relations between social ways of remembering and grief. Self-positive ways of remembering the deceased (Study 2) were associated with having experienced positive changes in life perspective since the loss. Conclusion: The discussion focuses on how memories of one's personal past are linked to the experience of loss, even years into bereavement.